Reduced fitness of Atlantic salmon released in the wild after one generation of captive breeding. (22nd November 2012) - Milot, Emmanuel; Perrier, Charles; Papillon, Lucie; Dodson, Julian J.; Bernatchez, Louis
Abstract Salmonids rank among the most socioeconomically valuable fishes and the most targeted species by stocking with hatchery‐reared individuals. Here, we used molecular parentage analysis to assess the reproductive success of wild‐ and hatchery‐born Atlantic salmon over three consecutive years in a small river in Québec. Yearly restocking in this river follows a single generation of captive breeding. Among the adults returning to the river to spawn, between 11% and 41% each year were born in hatchery. Their relative reproductive success (RRS) was nearly half that of wild‐born fish (0.55). RRS varied with life stage, being 0.71 for fish released at the fry stage and 0.42 for fish released as smolt. The lower reproductive success of salmon released as smolt was partly mediated by the modification of the proportion of single‐sea‐winter/multi‐sea‐winter fish. Overall, our results suggest that modifications in survival and growth rates alter the life‐history strategies of these fish at the cost of their reproductive success. Our results underline the potential fitness decrease, warn on long‐term evolutionary consequences for the population of repeated stocking and support the adoption of more natural rearing conditions for captive juveniles and their release at a younger stage, such as unfed fry.